Healthcare Services and Empathy: A Portrait of the Pharmacy Students on Determining the Empathy Levels - Sözen Şahne, Bilge; Yumrukaya, Leyla; Yaman, Uğur; Yeğenoğlu, Selen (Hacettepe University Journal of the Faculty of Pharmacy, 2024)
Empathy is defined as a fundamental tool to improve the healthcare professional-patient bond and understanding of both patient and other professionals which enhances the healthcare professional’s experience. The empathetic attitude of the pharmacist could be a key element in effective interaction and this skill can be improved with various methods. In this study, it is aimed to reveal whether pharmacy education has an effect on the level of empathy by comparing the opinions of the students and their empathy levels. The validated Turkish version of the Empathy Quotient (EQ) questionnaire was used to reveal the participants’ empathy level. 311 students participated in the survey from 699 students and 306 of them were included in the analysis. According to the scale scores’ mean of students, a statistically significant difference was found only in terms of gender. Additionally, whether they had an internship or not did not make a significant difference on empathy levels. Pharmacy students’ technical skills in providing therapeutic recommendations may be negatively affected by their inability to communicate or engage with patients due to their lack of empathy. To prevent this, empathy as a teachable ability could be involved in the pharmacy education curriculum with various practices and techniques.